Identification of the UL4 protein of herpes simplex virus type 1. - Eide, Truls; Marsden, Howard S; Leib, David A; Cunningham, Charles; Davison, Andrew J; Langeland, Nina; Haarr, Lars (Journal of General Virology, 1998)
Herpes simplex virus type 1 gene UL4 is predicted to encode a 199-amino-acid protein with a molecular mass of 21·5 kDa. We report here identification of this protein and its localization in the nuclei of infected cells. Antisera raised against oligopeptides corresponding to the C terminus of the predicted UL4 protein were used for identification of a 25 kDa protein as the product of the UL4 gene. This protein was not detected in cells infected with a UL4 defective mutant virus, but was synthesized by coupled in vitro transcription-translation of the UL4 gene. Synthesis of the 25 kDa protein was blocked by phosphonoacetic acid, an inhibitor of DNA synthesis, indicating that the UL4 gene is expressed with γ kinetics. Subcellular fractionation showed the protein to be localized in the nucleus. It was not detected in virions or light particles.